PENGEMBANGAN MEDIA MONOPOLI “GEMAS” DALAM MENINGKATKAN PENGETAHUAN PESAN UMUM GIZI SEIMBANG PADA SISWA SD KELAS IV (Politeknik Kesehatan Kemenkes Bandung, 2021)
Indonesia is currently facing a double nutrition problem. There are two types of malnutrition: undernutrition and overnutrition. Socialization activities of balanced nutrition guidelines are required to prevent the nutritional problems. Education through learning media in the form of educational games is one kind of health education that can be used. Monopoly games are a fun and instructive way to provide information. Referring to the problem, the research “Development of Monopoly Media